Manganese phosphate salt positive electrode material and preparation method and application thereof
By adding carbon sources step by step and using polymer carbon sources and using short-chain carbon sources to build a uniform carbon coating layer, the problem of poor retention rate of manganese phosphate-based positive electrode materials is solved, and the electrochemistry of the material is significantly improved Performance and cycle stability.
Patent Information
- Application Number
- CN202411215264.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-30
AI Technical Summary
The manganese phosphate salt-based positive electrode material has poor manganese platform retention rate during the circulation process, which affects the material's energy density and stability, resulting in poor cycle stability and electrochemical performance.
The manganese phosphate-based positive electrode material is prepared by step-by-step addition of carbon sources. Through the mixing of polymer carbon sources and short-chain carbon sources, a uniform carbon cladding layer is built to improve the structural stability and conductivity of the material and reduce free carbon. , enhance the retention rate of manganese platform.
The manganese platform retention, discharge specific capacity and rate performance of the manganese phosphate-based positive electrode material is significantly improved, the cyclic stability and electrochemical performance of the material are enhanced, and the energy density and cyclic stability of the secondary battery are improved.
Smart Images

Figure CN119118086A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and in particular relates to a manganese phosphate-based positive electrode material and a preparation method and application thereof. Background Art
[0002] In recent years, lithium-ion battery cathode materials have made great progress. Initially, lithium cobalt oxide (LiCoO 2 ) is the main material used, which has a higher energy density. Subsequently, in order to improve safety and reduce costs, lithium iron phosphate (LiFePO 4 , LFP) was developed with better thermal stability and longer cycle life. But LFP also has many shortcomings. First, their energy density is relatively low, which limits their use in applications with higher energy demands. Secondly, the performance of these batteries drops significantly in low temperature environments, affecting their efficiency in cold areas, and the charging speed of lithium iron phosphate batteries is slower than other types of lithium-ion batteries, which may affect applications that require fast charging.
[0003] Lithium iron manganese phosphate (LiFeMnPO 4 LMFP is a new type of positive electrode material for lithium-ion batteries, which combines the high safety of lithium iron phosphate and the high voltage characteristics of lithium manganese phosphate. This material has attracted people's attention due to its environmental protection and high energy density, but the presence of lithium manganese phosphate makes the electronic conductivity of the material worse than LFP. At the same time, the significant internal resistance in the lattice leads to an extremely low ion diffusion coefficient. These shortcomings make its stability during the cycle process have certain problems, especially the problem of the attenuation of the discharge platform retention rate of the manganese segment during the cycle. This has a huge impact on its high energy density advantage and is one of the problems that LMFP urgently needs to solve. Summary of the invention
[0004] The purpose of the present application is to provide a manganese phosphate salt-based positive electrode material and a preparation method and application thereof, aiming to solve the problem that the manganese platform retention rate of existing manganese phosphate salt-based positive electrode materials is poor, which affects the energy density and stability of the material.
[0005] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0006] In a first aspect, the present application provides a method for preparing a manganese phosphate-based positive electrode material, comprising the following steps:
[0007] Obtaining raw material components including a phosphorus source, a manganese source, a lithium source, other metal sources and an initial carbon source, preparing a first mixed slurry with the raw material components and a first solvent, and then drying the mixed slurry to obtain a primary mixed material; the mass percentage of the initial carbon source in the raw material components is 1% to 3%;
[0008] Under an inert atmosphere, the mixed material is subjected to a primary sintering treatment to obtain a primary sintered material;
[0009] The amount of additional carbon source required is calculated according to the carbon content in the primary sintered material and the target carbon content in the finished product, and the primary sintered material, the additional carbon source and the second solvent are made into a second mixed slurry and then dried to obtain a secondary mixed material; wherein the initial carbon source and the additional carbon source independently include a polymer carbon source and a short-chain carbon source respectively;
[0010] Under an inert atmosphere, the secondary mixed material is subjected to a secondary sintering treatment and then crushed to obtain the finished product, namely, the manganese phosphate-based positive electrode material.
[0011] In some possible implementations, the mass percentage of the initial carbon source in the raw material component is 1.5% to 2.5%.
[0012] In some possible implementations, the carbon content in the primary sintering material is 0.12% to 0.36%.
[0013] In some possible implementations, the amount of the additional carbon source added is 8% to 12% of the total mass of the primary sintering material and the additional carbon source.
[0014] In some possible implementations, the target carbon content in the finished product is 1.6% to 1.65%.
[0015] In some possible implementations, the actual carbon content in the manganese phosphate-based positive electrode material is 1.4% to 1.6%.
[0016] In some possible implementations, the D50 particle size of the manganese phosphate-based positive electrode material is 0.9 μm to 1.5 μm.
[0017] In some possible implementations, the compaction density of the manganese phosphate-based positive electrode material is greater than 2.19 g / cm 3 .
[0018] In some possible implementations, the specific surface area of the manganese phosphate-based positive electrode material is 15 m 2 / g~18m 2 / g.
[0019] In some possible implementations, the resistivity of the manganese phosphate-based positive electrode material is lower than 200Ω·cm.
[0020] In some possible implementations, the polymer carbon source includes at least one of polyethylene glycol, polyvinyl alcohol, polyacrylic acid, carboxymethyl cellulose, and starch.
[0021] In some possible implementations, the short-chain carbon source includes at least one of glucose, sucrose, and citric acid.
[0022] In some possible implementations, the other metal source includes at least one of an iron source, a niobium source, a titanium source, a cobalt source, a nickel source, and a vanadium source.
[0023] In some possible implementations, the first solvent and the second solvent each independently include water.
[0024] In some possible implementations, the molar ratio of the other metal source to the manganese source is (10-X):X, wherein X is 2-8.
[0025] In some possible implementations, the ratio of the total molar amount of the manganese source and the other metal source to the molar amount of the lithium source and the phosphorus source is 1:(1-1.03):(1-1.03).
[0026] In some possible implementations, the first mixed slurry is prepared by a sanding process, and a particle size D50 of a material in the slurry is 0.6 μm to 0.9 μm.
[0027] In some possible implementations, the conditions for drying the first mixed slurry include: spray drying under the conditions of an atomization frequency of 250 Hz to 350 Hz and an inlet air temperature of 150° C. to 250° C.
[0028] In some possible implementations, the heating rate of the primary sintering treatment is 1° C. / min to 10° C. / min, the holding temperature is 400° C. to 600° C., and the duration is 5 h to 8 h.
[0029] In some possible implementations, the second mixed slurry is prepared by a sanding process, and a particle size D50 of a material in the slurry is 0.6 μm to 0.9 μm.
[0030] In some possible implementations, the conditions for drying the second mixed slurry include: spray drying under the conditions of an atomization frequency of 250 Hz to 350 Hz and an inlet air temperature of 150° C. to 250° C.
[0031] In some possible implementations, the heating rate of the secondary sintering treatment is 1° C. / min to 10° C. / min, the holding temperature is 600° C. to 800° C., and the duration is 6 h to 10 h.
[0032] In a second aspect, the present application provides a manganese phosphate-based positive electrode material prepared by the above method, comprising a manganese phosphate-based active core and a carbon layer coated on the outer surface of the core; the carbon layer is made of a polymer carbon source and a short-chain carbon source.
[0033] In some possible implementations, the manganese phosphate-based active core includes lithium manganese iron phosphate.
[0034] In some possible implementations, the thickness of the carbon layer in the manganese phosphate-based positive electrode material is 1 nm to 5 nm.
[0035] In a third aspect, the present application provides a positive electrode sheet, comprising a current collector and a positive electrode active layer formed on the surface of the current collector, wherein the positive electrode active layer contains the above-mentioned manganese phosphate-based positive electrode material, or the manganese phosphate-based positive electrode material prepared by the above-mentioned method.
[0036] In a fourth aspect, the present application provides a secondary battery, wherein the secondary battery comprises the above-mentioned positive electrode sheet.
[0037] The preparation method of the manganese phosphate salt positive electrode material provided in the first aspect of the present application realizes the construction of a uniform carbon coating layer by a step-by-step method of adding a carbon source, effectively reducing the free carbon in the finished product, making fuller use of the carbon source, and improving the graphitization degree of the carbon coating layer. By adding the carbon source in steps, it is also found that the amount of carbon source added before the primary sintering treatment affects the physical and chemical properties such as the compaction density and specific surface area of the finished product, as well as the electrochemical properties such as the discharge specific capacity. In addition, the mass percentage of the initial carbon source in the raw material component is controlled at 1% to 3%. By controlling the amount of carbon source added before the primary sintering, the compaction, specific surface area, conductivity and other properties of the finished product can be effectively regulated. At the same time, this also has a very significant effect on the manganese platform retention rate, thereby improving the manganese platform retention rate. In addition, a mixed carbon source including a polymer carbon source and a short-chain carbon source is used, which can achieve uniform carbon layer coating and good electronic conductivity. Combining the advantages and disadvantages of the two carbon sources, the carbon source is fully utilized, effectively reducing the free carbon in the finished product. The use of a mixed carbon source can make the thickness of the carbon coating more uniform and the degree of graphitization higher, which is beneficial to inhibiting the dissolution of metal ions during the cycle of the material, reducing the side reactions at the negative electrode, and improving the stability of the battery.
[0038] In the second aspect of the present application, a manganese phosphate salt-based positive electrode material is prepared by the above method, comprising a manganese phosphate salt-based active core and a carbon layer coated on the outer surface of the core; the carbon layer is prepared from a polymer carbon source and a short-chain carbon source. The carbon layer is uniformly and stably coated on the surface of the manganese phosphate salt-based active core particles, which can not only improve the structural stability of the manganese phosphate salt-based positive electrode material, but also improve the conductivity of the manganese phosphate salt-based positive electrode material, improve the cycle stability of the manganese phosphate salt-based positive electrode material, improve the stability of the interface between the positive electrode material and the electrolyte, and alleviate the stress caused by volume change, which are all extremely beneficial to the manganese platform retention rate during the cycle of the manganese phosphate salt-based positive electrode material, can improve the manganese platform retention rate, and improve the electrochemical performance of the manganese phosphate salt-based positive electrode material.
[0039] In the positive electrode sheet of the third aspect of the present application, since the above-mentioned manganese phosphate-based positive electrode material is used in the positive electrode active layer, the manganese phosphate-based positive electrode material contains a manganese phosphate-based active core and a carbon layer covering the outer surface, which improves the conductivity, structural stability, high capacity and other characteristics of the manganese phosphate-based positive electrode material. Therefore, the stability, energy density, rate performance, cycle performance and other electrochemical properties of the positive electrode sheet are improved.
[0040] The secondary battery provided in the fourth aspect of the present application includes the positive electrode sheet with excellent electrochemical properties such as good stability, high energy density, good rate performance, and good cycle stability, thereby improving the electrochemical properties such as energy density and cycle stability of the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0042] Figure 1 It is a schematic flow chart of a method for preparing a manganese phosphate-based positive electrode material provided in an embodiment of the present application;
[0043] Figure 2 It is the XRD diagram of the lithium manganese iron phosphate positive electrode material prepared in Examples 1-3 and Comparative Examples 1-3 provided in the examples of the present application;
[0044] Figure 3 It is a SEM image of the lithium manganese iron phosphate positive electrode material prepared in Examples 1-3 and Comparative Examples 1-3 provided in the examples of the present application;
[0045] Figure 4 This is a TEM image of the lithium manganese iron phosphate positive electrode material prepared in Example 1 of the present application;
[0046] Figure 5 It is a charge and discharge curve diagram of the lithium iron manganese phosphate positive electrode material prepared in Examples 1-3 and Comparative Examples 1-3 provided in the embodiments of the present application under 0.1C and 1C conditions;
[0047] Figure 6 It is the discharge specific capacity of the lithium manganese iron phosphate positive electrode materials prepared in Examples 1-3 and Comparative Examples 1-3 provided in the present application when cycled under 1C conditions;
[0048] Figure 7 It is the discharge manganese platform retention rate of the lithium manganese iron phosphate positive electrode materials prepared in Examples 1-3 and Comparative Examples 1-3 provided in the examples of the present application when cycled under 1C conditions;
[0049] Figure 8 It is the discharge specific capacity of the lithium manganese iron phosphate positive electrode materials prepared in Examples 1-3 and Comparative Examples 1-3 provided in the present application under 1C conditions at 40°C;
[0050] Fig. 9 It is the discharge manganese platform retention rate of the lithium manganese iron phosphate positive electrode materials prepared in Examples 1-3 and Comparative Examples 1-3 provided in the examples of the present application when cycled under 1C conditions at 40°C;
[0051] Fig.10 The charge and discharge curves of the lithium manganese iron phosphate positive electrode material prepared in Examples 1-3 provided in the examples of the present application under 0.1C, 0.5C, 1C, 2C, and 3C conditions;
[0052] Fig.11 It is the proportion of the manganese stage discharge platform of the lithium iron manganese phosphate positive electrode material prepared in Examples 1-3 provided in the embodiments of the present application under the conditions of 0.1C, 0.5C, 1C, 2C, and 3C. DETAILED DESCRIPTION
[0053] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0054] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0055] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0056] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0057] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0058] The weight of the relevant components mentioned in the embodiments of the present specification can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components in the embodiments of the present specification is proportionally enlarged or reduced, it is within the scope disclosed in the embodiments of the present specification. Specifically, the mass described in the embodiments of the present specification can be μg, mg, g, kg and other mass units known in the chemical industry.
[0059] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0060] The first aspect of the present application provides a method for preparing a manganese phosphate-based positive electrode material, as shown in the attached Figure 1 As shown, the following steps are included:
[0061] S10. Obtaining a raw material component including a phosphorus source, a manganese source, a lithium source, other metal sources and an initial carbon source, preparing a first mixed slurry with the raw material component and a first solvent, and then drying the mixed slurry to obtain a primary mixed material; the mass percentage of the initial carbon source in the raw material component is 1% to 3%;
[0062] S20. Under an inert atmosphere, the mixed material is subjected to a sintering treatment to obtain a sintered material;
[0063] S30. Calculating the amount of additional carbon source required according to the carbon content in the primary sintered material and the target carbon content in the finished product, preparing a second mixed slurry with the primary sintered material, the additional carbon source and the second solvent, and drying the slurry to obtain a secondary mixed material; wherein the initial carbon source and the additional carbon source independently include a polymer carbon source and a short-chain carbon source;
[0064] S40. Under an inert atmosphere, the secondary mixed material is subjected to secondary sintering treatment and then crushed to obtain a finished product, namely, a manganese phosphate-based positive electrode material.
[0065] The method for preparing the manganese phosphate-based positive electrode material provided in the first aspect of the embodiment of the present application has at least the following beneficial effects:
[0066] First, the carbon source is added during the primary sintering treatment and the secondary sintering treatment, respectively. The construction of a uniform carbon coating layer is achieved by adding the carbon source in a step-by-step manner, which effectively reduces the free carbon in the finished product, makes more full use of the carbon source, and improves the graphitization degree of the carbon coating layer. This can inhibit the dissolution of metal ions such as Mn and Fe in the manganese phosphate-based positive electrode material during the cycle, which is beneficial to improving the manganese platform retention rate of the manganese phosphate-based positive electrode material during the cycle. In addition, by adding the carbon source in steps, it was also found that the amount of carbon source added before the primary sintering treatment affects the physical and chemical properties of the finished product, such as the compacted density and specific surface area, as well as the electrochemical properties such as the discharge specific capacity.
[0067] Secondly, the present application embodiment study found that the amount of carbon content in the first sintering has a significant effect on the performance of the finished product. Therefore, before the first sintering process, the mass percentage of the initial carbon source in the raw material component is controlled at 1% to 3%, and the amount of carbon source required for the secondary sintering process is calculated according to the carbon content in the first sintering material and the carbon target content in the finished product. By controlling the amount of carbon source added before the first sintering, the compaction, specific surface area, conductivity and other properties of the finished product can be effectively regulated, and this also has a very significant effect on the manganese platform retention rate. If too much carbon source is added before the first sintering, the amount of carbon source added after the first sintering is too little, which is easy to cause the formation of more extremely small particles and serious agglomeration. At this time, the carbon supplementation effect on the finished product is not good, which is not conducive to improving the performance of the finished product. If too little carbon source is added before the first sintering, it may cause the metal components such as the manganese source to be unable to be fully reduced during the sintering process, which is not conducive to the formation of manganese phosphate salt positive electrode material crystal nuclei. In this case, there will be more impurities in the prepared finished product, so an appropriate amount of carbon source should be added before the first sintering.
[0068] Third, the use of a mixed carbon source including a polymer carbon source and a short-chain carbon source can achieve uniform carbon layer coating while also having good electronic conductivity. Short-chain carbon sources are small molecule carbon sources that can increase the specific surface area of the material, increase the reaction sites and electronic conductivity, but will produce uneven coating and cannot effectively inhibit the dissolution of transition metals; polymer carbon sources are high molecular polymers, which are conducive to the formation of a thin film of carbon coating when used as a carbon source, which can reduce the specific surface area of the material and increase the compaction density of the material, but the electronic conductivity of the material will usually decrease. Therefore, the mixed carbon source used combines the advantages and disadvantages of the two carbon sources, so that the carbon source is fully utilized, effectively reducing the free carbon in the finished product, and the use of a mixed carbon source can make the thickness of the carbon coating layer more uniform and the degree of graphitization higher, which is beneficial to inhibit the dissolution of metal ions during the material cycle, reduce the side reactions occurring at the negative electrode, and improve the stability of the battery.
[0069] Therefore, the preparation method of the manganese phosphate salt-based positive electrode material in the embodiment of the present application effectively improves the manganese platform retention rate of the prepared manganese phosphate salt-based positive electrode material during normal temperature and high temperature cycles, greatly improves the discharge specific capacity of the material, and has excellent rate performance, with outstanding multiple charge and discharge capabilities.
[0070] In the above step S10: after the phosphorus source, manganese source, lithium source, other metal sources and initial carbon source are dissolved and dispersed in the first solvent, a sand milling process is performed to mix the materials to prepare a first mixed slurry.
[0071] In some possible implementations, the first solvent includes water, which has good dissolution and dispersion properties for the raw material components and can prevent solvent residues from affecting subsequent sintering processing and finished product performance.
[0072] In some possible implementations, the initial carbon source includes a polymer carbon source and a short-chain carbon source. In this case, the mixed carbon source used combines the advantages and disadvantages of the two carbon sources, making full use of the carbon source, effectively reducing the free carbon in the finished product, making the carbon coating layer more uniform in thickness, and having a higher degree of graphitization, which is beneficial to reducing the side reactions occurring at the negative electrode and improving the electrochemical properties of the material, such as stability.
[0073] In some possible implementations, the polymer carbon source includes at least one of polyethylene glycol, polyvinyl alcohol, polyacrylic acid, carboxymethyl cellulose, and starch. These high molecular polymers, when used as carbon sources, are conducive to forming a film-like carbon coating layer, which can reduce the specific surface area of the material and increase the compaction density of the material.
[0074] In some possible implementations, the short-chain carbon source includes at least one of glucose, sucrose, and citric acid. These small molecule carbon sources can increase the specific surface area of the material, increase the reaction sites and electronic conductivity.
[0075] In some embodiments, the mass ratio of the polymer carbon source to the short-chain carbon source can be 1:1, 1:2, 2:1, 1:3, 3:1, or any other typical but non-limiting value, or an interval value between any two values.
[0076] In some possible implementations, the manganese source includes one or more of manganese chloride tetrahydrate, manganese sulfate, manganese nitrate, manganese acetate tetrahydrate, and manganese dioxide.
[0077] In some possible implementations, the lithium source includes one or more of lithium dihydrogen phosphate, lithium hydroxide, lithium carbonate, and lithium acetate.
[0078] In some possible implementations, the phosphorus source includes one of ammonium dihydrogen phosphate and lithium dihydrogen phosphate.
[0079] In some possible implementations, other metal sources include: at least one of an iron source, a niobium source, a titanium source, a cobalt source, a nickel source, and a vanadium source; and by doping these metal elements, the electrochemical properties of the manganese phosphate-based positive electrode material can be further improved.
[0080] In some possible implementations, the iron source includes one or more of ferric sulfate, anhydrous ferric chloride, ferric chloride hexahydrate, ferric nitrate nonahydrate, ferric oxide, and ferrosoferric oxide.
[0081] The raw material components used in the above embodiments of the present application are of high purity, and all of the above raw material components have good solubility, which is conducive to the preparation of manganese phosphate-based positive electrode active materials.
[0082] In some possible implementations, the molar ratio of other metal sources and manganese sources is (10-X):X, where X is 2-8, and can be 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, or other typical but non-limiting arbitrary point values or an interval value between any two point values.
[0083] In some possible implementations, the ratio of the total molar amount of manganese source and other metal sources to the molar amount of lithium source and phosphorus source is 1:(1-1.03):(1-1.03). In this case, the appropriate increase of Li source helps to refine the grains, alleviate the sintering and fusion between grains, and help improve the rate discharge performance of manganese phosphate-based positive electrode materials. The appropriate increase of phosphorus source relative to metal sources such as manganese promotes the growth of primary particles and can reduce particle agglomeration.
[0084] In some possible implementations, the manganese phosphate-based positive electrode material is lithium manganese iron phosphate, and the iron source, manganese source, phosphorus source, lithium source and initial carbon source are dispersed in deionized water, and then sand-milled to mix the materials evenly to obtain a first mixed slurry. The iron source and manganese source are added in a molar ratio of Fe to Mn of 4:6; the lithium source and phosphorus source are added in a ratio of Li:P:(Fe+Mn)=1.03:1.03:1.0.
[0085] In some possible implementations, the mass percentage of the initial carbon source in the raw material component is 1.5% to 2.5%; specifically, it can be 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, and other typical but non-restrictive arbitrary point values or interval values between any two point values. In this case, the carbon content added during the primary sintering and secondary sintering processes is more conducive to improving the coating effect of the carbon material on the active material, improving the particle size, specific surface area, morphology and other characteristics of the manganese phosphate salt positive electrode material, thereby better improving the compaction density, active specific surface area and other physicochemical properties of the manganese phosphate salt positive electrode material, and improving the capacity, cycle stability, rate and other electrochemical properties of the manganese phosphate salt positive electrode material.
[0086] In some possible implementations, the first mixed slurry is obtained by a sanding process, and the particle size D50 of the material in the slurry is 0.6μm to 0.9μm, which can be any typical but non-restrictive point value such as 0.6μm, 0.7μm, 0.8μm, 0.9μm, or an interval value between any two point values. In this case, the material is mixed by sanding, and the sanding process ensures the uniformity of the material mixing, and can also regulate the particle size distribution of the material. In addition, the particle size D50 of the material in the slurry is 0.6μm to 0.9μm. Within this particle size range, it can not only ensure the full mixing of the raw materials, but also minimize the number of extremely small particle debris, because the more times the sanding is performed, the greater the difference in the particle size of the large and small particles will be. The qualified particle size of sanding within this range can make the particle size of the finished product more concentrated and uniform.
[0087] In some possible implementations, the conditions for drying the first mixed slurry include: spray drying under the conditions of atomization frequency conversion of 250Hz to 350Hz and inlet air temperature of 150℃ to 250℃. In this case, the material is dried by spray drying and the morphology of the finished particles is regulated to a certain extent; the spray drying process can regulate the morphology of the material to make it more spherical and more conducive to the performance of electrical properties. Exemplarily, the atomization frequency conversion of spray drying can be 250Hz, 260Hz, 280Hz, 300Hz, 320Hz, 350Hz, etc., typical but non-restrictive arbitrary point values or interval values between any two point values; the inlet air temperature can be 150℃, 160℃, 180℃, 200℃, 220℃, 250℃, etc., typical but non-restrictive arbitrary point values or interval values between any two point values.
[0088] In the above step S20:
[0089] In some possible implementations, the heating rate of the primary sintering treatment is 1°C / min to 10°C / min, the holding temperature is 400°C to 600°C, and the duration is 5h to 8h. In this case, the manganese phosphate salt is the initial formation process of the positive electrode material during the primary sintering process, and the particle size and the discharge of volatile matter can be well balanced. If the temperature is high or the sintering time is long, the crystal grows faster, and not enough carbon is added at the beginning to cover and limit the growth of the particles. Therefore, the particle size after the primary sintering is too large, which will make the average primary particle size of the finished product (the particle size calculated by the SEM image) larger and the difference between large and small particles greater, which is not conducive to electrochemical performance. On the contrary, if the temperature is low or the sintering time is short, the crystal nucleus is initially generated. Although the particles will not grow excessively, the volatile components therein are not removed cleanly, the amount of carbon source supplemented during sand grinding will be reduced, and more volatile substances will continue to be produced during the subsequent secondary sintering, which is extremely unfavorable for compaction.
[0090] Exemplarily, the heating rate of a sintering treatment can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, or any other typical but non-limiting point value or an interval value between any two point values; the holding temperature can be 400°C, 450°C, 500°C, 550°C, 600°C, or any other typical but non-limiting point value or an interval value between any two point values; the duration can be 5h, 6h, 7h, 8h, or any other typical but non-limiting point value or an interval value between any two point values.
[0091] In some possible implementations, during the primary sintering process, the inert atmosphere includes at least one of nitrogen, argon, and helium.
[0092] In some possible implementations, the carbon content in the primary sintered material is 0.12% to 0.36%. In this case, the carbon content in the primary sintered material is conducive to regulating the compaction, specific surface area, conductivity and other properties of the finished product, and it also has a very significant effect on the manganese platform retention rate. Exemplarily, the carbon content in the primary sintered material can be 0.12%, 0.15%, 0.18%, 0.20%, 0.23%, 0.25%, 0.28%, 0.30%, 0.33%, 0.36% and other typical but non-restrictive arbitrary point values or interval values between any two point values.
[0093] In the above step S30: the carbon content in the primary sintered material is detected, and then the amount of additional carbon source required is calculated based on the carbon content in the primary sintered material and the target carbon content in the finished product. The finished product refers to the target product manganese phosphate salt positive electrode material prepared. The amount of carbon source added here is positively correlated with the carbon content of the finished product. After the carbon content in the primary sintered material is measured, the required amount of additional carbon source can be calculated according to the target carbon content in the finished product. Based on this, the amount of carbon source required to be added during the secondary sintering process can be obtained.
[0094] In some embodiments, the amount of additional carbon source can be calculated according to the formula: additional carbon source = mass of primary sintered material * (target carbon content in finished product - carbon content in primary sintered material) * K, where K is an adjustment coefficient, which is used to adjust the original data to eliminate the influence of different dimensions, data ranges or system errors on the calculation results. By adjusting the coefficient, data from different sources or under different conditions can be made comparable, thereby improving the accuracy and reliability of the analysis. For example, K = 2 to 10.
[0095] In some possible implementations, the target carbon content in the finished product is 1.6% to 1.65%, and can be any typical but non-restrictive point value or an interval value between any two point values such as 1.6%, 1.61%, 1.62%, 1.63%, 1.64%, 1.65%. In this case, the carbon content in the finished product can form a complete and uniform coating layer, improve the particle size, specific surface area, morphology and other characteristics of the manganese phosphate salt positive electrode material, thereby improving the compaction density, active specific surface area, cycle stability and other properties of the manganese phosphate salt positive electrode material, and is also conducive to ensuring the capacity of the manganese phosphate salt positive electrode material.
[0096] In some possible implementations, the amount of additional carbon source required is calculated based on the carbon content in the primary sintered material and the target carbon content in the finished product, and the amount of additional carbon source added is 8% to 12% of the total mass of the primary sintered material and the additional carbon source. In this case, the amount of additional carbon source is conducive to forming a complete carbon coating layer, improving the morphology of the manganese phosphate positive electrode material, and controlling the actual carbon content in the manganese phosphate positive electrode material to about 1.6%, thereby improving the electrochemical performance of the manganese phosphate positive electrode material. Exemplarily, the amount of additional carbon source added is 8%, 9%, 10%, 11%, 12% of the total mass of the primary sintered material and the additional carbon source, or an interval value between any two points.
[0097] In some possible implementations, the second solvent includes water, which has good solubility and dispersion properties for the primary sintering material and the supplementary carbon source.
[0098] In some possible implementations, the added carbon source includes a polymer carbon source and a short-chain carbon source. In some possible implementations, the polymer carbon source includes at least one of polyethylene glycol, polyvinyl alcohol, polyacrylic acid, carboxymethyl cellulose, and starch. In some possible implementations, the short-chain carbon source includes at least one of glucose, sucrose, and citric acid. In this case, the mixed carbon source used combines the advantages and disadvantages of the two carbon sources, so that the carbon source is fully utilized, the free carbon in the finished product is effectively reduced, the thickness of the carbon coating layer is more uniform, and the degree of graphitization is higher, which is beneficial to reduce the side reactions occurring at the negative electrode and improve the electrochemical properties such as the stability of the material.
[0099] In some possible implementations, the second mixed slurry is obtained by a sanding process, and the particle size D50 of the material in the slurry is 0.6μm to 0.9μm; specifically, it can be any typical but non-restrictive point value such as 0.6μm, 0.7μm, 0.8μm, 0.9μm, or an interval value between any two point values. In this case, the material is mixed by sanding, and the sanding process ensures the uniformity of the material mixing, and can also regulate the particle size distribution of the material. In addition, the particle size D50 of the material in the slurry is 0.6μm to 0.9μm. Within this particle size range, it can not only ensure the full mixing of the raw materials, but also minimize the number of extremely small particle debris, because the more times the sanding is performed, the greater the difference in particle size between large and small particles will be. The qualified particle size of sanding within this range can make the particle size of the finished product more concentrated and uniform.
[0100] In some possible implementations, the conditions for drying the second mixed slurry include: spray drying under the conditions of atomization frequency conversion of 250Hz to 350Hz and inlet air temperature of 150℃ to 250℃. In this case, the material is dried by spray drying and the morphology of the finished particles is regulated to a certain extent; the spray drying process can regulate the morphology of the material to make it more spherical and more conducive to the performance of electrical properties. Exemplarily, the atomization frequency conversion of spray drying can be 250Hz, 260Hz, 280Hz, 300Hz, 320Hz, 350Hz, etc., typical but non-limiting any point value or an interval value between any two point values; the inlet air temperature can be 150℃, 160℃, 180℃, 200℃, 220℃, 250℃, etc., typical but non-limiting any point value or an interval value between any two point values.
[0101] In the above step S40:
[0102] In some possible implementations, the heating rate of the secondary sintering treatment is 1°C / min to 10°C / min, the holding temperature is 600°C to 800°C, and the duration is 6h to 10h. In this case, the lithium manganese iron phosphate crystals can be made more complete and have a higher crystallinity, and it is beneficial to improve the graphitization degree of the carbon coating layer.
[0103] Exemplarily, the heating rate of the secondary sintering treatment can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, etc., typical but non-limiting arbitrary point values or interval values between any two point values; the holding temperature can be 600°C, 650°C, 700°C, 750°C, 800°C, etc., typical but non-limiting arbitrary point values or interval values between any two point values; the duration can be 6h, 7h, 8h, 9h, 10h, etc., typical but non-limiting arbitrary point values or interval values between any two point values.
[0104] In some possible implementations, during the secondary sintering process, the inert atmosphere includes at least one of nitrogen, argon, and helium.
[0105] In some possible implementations, the sintered product is ground into powder by a jet mill. In some embodiments, the frequency of the classifying wheel of the jet mill is between 40 Hz and 60 Hz.
[0106] In some possible implementations, the actual carbon content in the manganese phosphate-based positive electrode material is 1.4% to 1.6%. In this case, the actual carbon content in the manganese phosphate-based positive electrode material can form a complete and uniform coating layer, improve the particle size, specific surface area, morphology and other properties of the manganese phosphate-based positive electrode material, thereby improving the compaction density, active specific surface area, cycle stability and other properties of the manganese phosphate-based positive electrode material, and is also conducive to ensuring the capacity of the manganese phosphate-based positive electrode material. Exemplarily, the actual carbon content in the manganese phosphate-based positive electrode material can be 1.4%, 1.5%, 1.6%, or any typical but non-restrictive point value or an interval value between any two point values.
[0107] In some possible implementations, the D50 particle size of the manganese phosphate-based positive electrode material is 0.9 μm to 1.5 μm. In this case, the particle size of the manganese phosphate-based positive electrode material is small, the active specific surface area is high, and it is conducive to ion insertion and extraction, thereby improving the rate performance of the manganese phosphate-based positive electrode material. Exemplarily, the D50 particle size of the manganese phosphate-based positive electrode material can be 0.9 μm, 0.933 μm, 1 μm, 1.13 μm, 1.2 μm, 1.3 μm, 1.35 μm, 1.4 μm, 1.5 μm, etc., typical but non-limiting arbitrary point values or interval values between any two point values.
[0108] In some possible implementations, the compaction density of the manganese phosphate-based positive electrode material is greater than 2.19 g / cm 3In this case, the compaction density of the manganese phosphate-based positive electrode material is high, which is conducive to improving the capacity of the manganese phosphate-based positive electrode material and providing the energy density of the positive electrode sheet. For example, the compaction density of the manganese phosphate-based positive electrode material can be 2.199 g / cm 3 , 2.319g / cm 3 , 2.269g / cm 3 , 2.49g / cm 3 , 2.59g / cm 3 , 2.69g / cm 3 , 2.79g / cm 3 , 2.89g / cm 3 , 2.99g / cm 3 、3.19g / cm 3 、3.39g / cm 3 、3.59g / cm 3 Typical but non-restrictive arbitrary point values or interval values between any two point values.
[0109] In some possible implementations, the specific surface area of the manganese phosphate-based positive electrode material is 15 m 2 / g~18m 2 / g; In this case, the manganese phosphate-based positive electrode material has a higher specific surface area, which improves the working efficiency of the material and also makes the manganese phosphate-based positive electrode material have better electrode sheet processing performance. For example, the specific surface area of the manganese phosphate-based positive electrode material can be 15m 2 / g, 16m 2 / g, 17m 2 / g, 18m 2 / g and other typical but non-limiting arbitrary point values or interval values between any two point values.
[0110] In some possible implementations, the resistivity of the manganese phosphate-based positive electrode material is lower than 200Ω·cm. In this case, the manganese phosphate-based positive electrode material has a low resistivity and high conductivity, which is conducive to the transmission of ions and electrons, and improves the charge and discharge rate performance of the manganese phosphate-based positive electrode material. Exemplarily, the resistivity of the manganese phosphate-based positive electrode material can be 197.2Ω·cm, 180Ω·cm, 170Ω·cm, 160Ω·cm, 150Ω·cm, 120Ω·cm, 100Ω·cm, 80Ω·cm, 60Ω·cm, 51.1Ω·cm, 50Ω·cm, 40Ω·cm, etc., typical but non-limiting arbitrary point values or interval values between any two point values.
[0111] In a second aspect, an embodiment of the present application provides a manganese phosphate-based positive electrode material prepared by the above method, comprising a manganese phosphate-based active core and a carbon layer coated on the outer surface of the core; the carbon layer is made of a polymer carbon source and a short-chain carbon source.
[0112] The manganese phosphate salt positive electrode material of the embodiment of the present application is prepared by the above method, including a manganese phosphate salt active core and a carbon layer coated on the outer surface of the core; the carbon layer is made of a polymer carbon source and a short-chain carbon source. The carbon layer is uniformly and stably coated on the surface of the manganese phosphate salt active core particles, which can not only improve the structural stability of the manganese phosphate salt positive electrode material, but also improve the conductivity of the manganese phosphate salt positive electrode material, improve the cycle stability of the manganese phosphate salt positive electrode material, improve the stability of the interface between the positive electrode material and the electrolyte, and alleviate the stress caused by volume change. These are all very beneficial to the manganese platform retention rate during the cycle of the manganese phosphate salt positive electrode material, improve the manganese platform retention rate of the manganese phosphate salt positive electrode material during normal temperature and high temperature cycles, greatly improve the discharge specific capacity of the material, and the rate performance is also very excellent, with excellent double charge and discharge capabilities, thereby significantly improving the electrochemical performance of the manganese phosphate salt positive electrode material.
[0113] In some possible implementations, the manganese phosphate-based active core includes lithium iron manganese phosphate, which combines the high safety of lithium iron phosphate with the high voltage characteristics of lithium manganese phosphate.
[0114] In some possible implementations, the thickness of the carbon layer in the manganese phosphate-based positive electrode material is 1 nm to 5 nm. In this case, it is beneficial to improve the structure and cycle stability of the manganese phosphate-based positive electrode material, and improve the electrochemical properties such as the conductivity of the manganese phosphate-based positive electrode material. Exemplarily, the thickness of the carbon layer in the manganese phosphate-based positive electrode material can be 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, etc., typical but non-limiting arbitrary point values or interval values between any two point values.
[0115] In a third aspect, an embodiment of the present application provides a positive electrode sheet, including a current collector and a positive electrode active layer formed on the surface of the current collector, the positive electrode active layer containing the above-mentioned manganese phosphate salt-based positive electrode material, or the manganese phosphate salt-based positive electrode material prepared by the above-mentioned method.
[0116] In the positive electrode sheet of the present application embodiment, since the above-mentioned manganese phosphate-based positive electrode material is used in the positive electrode active layer, the manganese phosphate-based positive electrode material contains a manganese phosphate-based active core and a carbon layer covering the outer surface, which improves the conductivity, structural stability, high capacity and other characteristics of the manganese phosphate-based positive electrode material. Therefore, the stability, energy density, rate performance, cycle performance and other electrochemical properties of the positive electrode sheet are improved.
[0117] In some possible implementations, the preparation of the positive electrode active layer includes the steps of: mixing the above-mentioned manganese phosphate-based positive electrode material, conductive agent and binder to form an electrode slurry, coating the electrode slurry on a current collector, and preparing a positive electrode sheet through steps such as drying, rolling and die cutting.
[0118] In some possible implementations, the mass percentage of the manganese phosphate-based positive electrode material in the positive electrode active layer of the positive electrode sheet is 90% to 95%. Specifically, the mass percentage of the manganese phosphate-based positive electrode material in the positive electrode active material layer can be 90%, 91%, 92%, 93%, 94%, 95%, etc.
[0119] In some possible implementations, the current collector of the positive electrode sheet includes but is not limited to any one of copper foil and aluminum foil.
[0120] In some possible implementations, the content of the binder in the active material layer of the positive electrode sheet is 2 wt% to 5 wt%. In specific embodiments, the content of the binder can be 2 wt%, 3 wt%, 4 wt%, 5 wt%, etc., which are typical but not limiting contents.
[0121] In some possible implementations, the binder includes one or more of polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan, and chitosan derivatives.
[0122] In some possible implementations, the content of the conductive agent in the active material layer of the positive electrode sheet is 1 wt% to 5 wt%. In specific embodiments, the content of the conductive agent can be 3 wt%, 4 wt%, 5 wt%, etc., which are typical but not limiting contents.
[0123] In some possible implementations, the conductive agent includes graphite, carbon black, acetylene black, graphene, carbon fiber, C 60 and one or more of carbon nanotubes.
[0124] In a fourth aspect, an embodiment of the present application provides a secondary battery, wherein the secondary battery comprises the above-mentioned positive electrode sheet.
[0125] The secondary battery provided in the embodiment of the present application includes the positive electrode sheet with excellent electrochemical properties such as good stability, high energy density, good rate performance, and good cycle stability, thereby improving the electrochemical properties of the secondary battery such as energy density and cycle stability.
[0126] The present application does not specifically limit the negative electrode sheet, electrolyte, separator, etc. in the secondary battery of the embodiment, and can be applied to any battery system.
[0127] In some possible implementations, the negative electrode active material of the secondary battery includes, but is not limited to, carbon materials such as graphite, soft carbon (such as coke), hard carbon, or nitrides, tin-based oxides, tin-based oxides, tin alloys, and nano-negative electrode materials, etc. The current collector includes, but is not limited to, any one of copper foil and aluminum foil.
[0128] In some possible embodiments, the steps of making a negative electrode sheet include: mixing a negative electrode active material with a conductive agent such as conductive carbon black, a binder such as carboxymethyl cellulose and styrene-butadiene rubber, and a solvent such as water in a mass ratio of (80-99):(1-5):(2-10):100 to make a negative electrode mixed slurry, vacuum degassing, discharging, coating on a coating machine, and obtaining a negative electrode sheet after rolling, slitting, and die-cutting.
[0129] In some possible implementations, the separator can block the passage of electrons and allow the passage of ions. Exemplarily, the separator includes, but is not limited to, at least one material selected from polypropylene fiber, polyacrylonitrile fiber, polyvinyl formal fiber, poly(ethylene terephthalate), polyethylene terephthalate, polyamide fiber, and poly(p-phenylene terephthalamide).
[0130] In some possible implementations, the electrolyte includes at least one soluble metal salt. In some specific embodiments, the metal salt includes LiClO 4 , LiBF 4 、LiPF 6 、LiAsF 6 、LiCF 3 SO 3 、LiTDI、Li[(CF 3 SO 2 ) 2 N]、Li[(FSO 2 ) 2 N]、Li[(C m F 2m+1 SO 2 )(C n F 2n+1 SO 2 )N], wherein m and n are natural numbers. These electrolytic salts can ensure high ionic conductivity of the electrolyte, and do not cause harmful side reactions with electrode materials, electrolytes, diaphragms, etc., and have good chemical stability.
[0131] In some possible implementations, the secondary battery includes at least one of a battery cell, a battery module, and a battery pack.
[0132] In some possible implementations, the battery cell types include lithium-ion batteries, as well as new batteries such as lithium-air batteries and lithium metal batteries.
[0133] In some possible implementations, the battery cells of the present application can be assembled into a battery module, and the number of battery cells contained in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module. Further, the battery module can also include a housing with a storage space, and multiple battery cells are stored in the storage space.
[0134] In a possible implementation, the battery cells and / or battery modules may also be assembled into a battery pack, and the number of battery cells or battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0135] In order to enable the above implementation details and operations of the present application to be clearly understood by those skilled in the art, as well as to demonstrate the significant improvement in the performance of the manganese phosphate-based positive electrode material and its preparation method and application in the embodiments of the present application, the above technical solution is illustrated by multiple embodiments below.
[0136] Example 1
[0137] A lithium manganese iron phosphate, the preparation of which comprises the following steps:
[0138] 1. Add 276.18g (1.83mol) of iron phosphate and 238.81g (2.75mol) of manganese dioxide to 3kg of deionized water, stir thoroughly for 3-5min with a tool, then add 169.13g (2.29mol) of lithium carbonate, stir thoroughly for 3-5min with a tool, then add 10g of glucose and 10g of polyvinyl alcohol, continue to mix thoroughly with a tool, and finally slowly add 316.33g (2.75mol) of diammonium phosphate. It can be seen that bubbles are generated after adding. This is because diammonium phosphate reacts with lithium carbonate to generate CO 2 Gas, in the designed LMFP, Mn:Fe=6:4, the solid content is about 30%, the mass of carbon source added is 2% of the total feed mass, and the mass ratio of the two carbon sources is 1:1. After the reaction is completed and the materials are fully mixed, sand milling begins. The feed speed is controlled by adjusting the peristaltic pump, and the sand milling particle size D50 is controlled between 0.6 and 0.9 μm. The sand milled material is spray dried, the feed speed is controlled by controlling the diaphragm pump, the atomization frequency is adjusted at 280 Hz, the air inlet temperature is adjusted at 200 ° C, and the material is dried.
[0139] 2. Place the dried material in a large sintering boat and sinter it in a tubular furnace under nitrogen atmosphere protection conditions. Raise the temperature from room temperature to 500°C at a rate of 5°C / min and sinter for 6 hours. Take it out after the temperature drops to room temperature to obtain a primary sintered sample.
[0140] 3. Test the carbon content of the sintered sample once, calculate the amount of carbon source to be added according to the finished product carbon content of 1.6%, and still add glucose and polyvinyl alcohol in a mass ratio of 1:1, and add 10% of the carbon source of the feed mass, that is, 50g glucose and 50g polyvinyl alcohol. Mix the sintered sample once and add the carbon source, and continue to use the sand grinding method to control the sand grinding particle size D50 between 0.6μm and 0.9μm. Spray dry the sand-ground material, control the feed speed by controlling the diaphragm pump, adjust the atomization frequency conversion at 280Hz, and the inlet air temperature at 200℃, and wait for the material to be dried.
[0141] 4. Place the dried material in a large calcining boat and sinter it in a tubular furnace under nitrogen atmosphere protection. Raise the temperature from room temperature to 750°C at a heating rate of 5°C / min, sinter for 8 hours, and take it out after the temperature drops to room temperature to obtain the second calcined sample. The second calcined sample is crushed by air jet mill, and the frequency of the classifying wheel is controlled at 40Hz. The crushed sample is the finished product of lithium manganese iron phosphate.
[0142] Example 2
[0143] A lithium manganese iron phosphate, which is different from Example 1 in that: in step 1, the mass of carbon source added is 1% of the total feed mass, that is, 5g of glucose and 5g of polyvinyl alcohol are added. Correspondingly, in step 3, 11% of the feed mass of carbon source, that is, 55g of glucose and 55g of polyvinyl alcohol, are added.
[0144] Example 3
[0145] A lithium manganese iron phosphate, which differs from Example 1 in that: in step 1, the mass of carbon source added is 3% of the total feed mass, that is, 15g of glucose and 15g of polyvinyl alcohol are added. Correspondingly, in step 3, 9% of the feed mass of carbon source, that is, 45g of glucose and 45g of polyvinyl alcohol, are added.
[0146] Comparative Example 1
[0147] A lithium manganese iron phosphate, the preparation of which comprises the following steps:
[0148] 1. Add 276.18g (1.83mol) of iron phosphate and 238.81g (2.75mol) of manganese dioxide to 3kg of deionized water, stir thoroughly for 3-5min with a tool, then add 169.13g (2.29mol) of lithium carbonate, stir thoroughly for 3-5min with a tool, then add a certain amount of glucose and a certain amount of polyvinyl alcohol, continue to mix thoroughly with a tool, and finally slowly add 316.33g (2.75mol) of diammonium phosphate. It can be seen that bubbles are generated after adding. This is because diammonium phosphate reacts with lithium carbonate to generate CO 2Gas, in the designed LMFP, Mn:Fe=6:4, and the solid content is about 30%. The mass of carbon source to be added is calculated based on the carbon content of the finished product of 1.6%, and the mass ratio of glucose to polyvinyl alcohol is 1:1. After the reaction is completed and the materials are fully mixed, sand milling begins. The feed speed is controlled by adjusting the peristaltic pump, and the sand milling particle size D50 is controlled between 0.6μm and 0.9μm. The sand milled material is spray dried, and the feed speed is controlled by controlling the diaphragm pump, the atomization frequency is adjusted at 280Hz, and the air inlet temperature is adjusted at 200℃, and the material is dried.
[0149] 2. Place the dried material in a large sintering boat and sinter it in a tubular furnace under nitrogen atmosphere protection conditions. Raise the temperature from room temperature to 500°C at a rate of 5°C / min and sinter for 6 hours. Take it out after the temperature drops to room temperature to obtain a primary sintered sample.
[0150] 3. The material after the primary sintering is simply crushed by a high-speed mixer and placed in a large sintering boat. It is sintered in a tubular furnace under nitrogen atmosphere protection conditions. The temperature is increased from room temperature to 750°C at a heating rate of 5°C / min and sintered for 8 hours. After the temperature drops to room temperature, it is taken out to obtain the second sintered sample.
[0151] 4. The sample after the second calcination is crushed by air flow mill, and the frequency of the classifying wheel is controlled at 40Hz. The crushed sample is the finished product of lithium manganese iron phosphate.
[0152] Comparative Example 2
[0153] A lithium manganese iron phosphate, which differs from Example 1 in that the carbon source added in step 1 is only glucose, that is, the amount of glucose added is 20g, and the other steps are consistent with Example 1.
[0154] Comparative Example 3
[0155] A lithium manganese iron phosphate, which differs from Example 1 in that: the carbon source added in step 1 is only polyvinyl alcohol, that is, the added amount of polyvinyl alcohol is 20g, and the other steps are consistent with Example 1.
[0156] Furthermore, in order to verify the progress of the embodiments of the present application, the following performance tests were performed on the above embodiments and comparative examples respectively:
[0157] 1. Carbon content test in primary sintered samples: using HCS-140 high frequency infrared carbon and sulfur analyzer;
[0158] 2. Carbon content test in finished lithium manganese iron phosphate products: using HCS-140 high-frequency infrared carbon and sulfur analyzer;
[0159] 3. D50 test of finished lithium manganese iron phosphate particle size: using Malvern 3000 laser particle size analyzer;
[0160] 4. Compacted density test of finished lithium iron manganese phosphate products: using electronic pressure testing machine UTM7305;
[0161] 5. Specific surface area test of finished lithium manganese iron phosphate: using JW-DX dynamic adsorption specific surface instrument degassing station (JW-TQ-D4) of JW-TQ-D4;
[0162] 6. Resistivity test of lithium iron manganese phosphate finished product: using ST2742B automatic powder resistivity tester;
[0163] The above test results are shown in Table 1 below:
[0164] Table 1
[0165]
[0166]
[0167] From the test results in Table 1 above, it can be seen that the carbon content of the once sintered sample has a significant effect on the conventional properties of the finished product. With the increase in the amount of carbon source added before the first sintering, the compaction of the material continues to decrease, the specific surface area first decreases and then increases, the resistance continues to increase, and D50 first decreases and then increases. Therefore, the amount of carbon source added before the first sintering can be used to adjust the various indicators of the finished product to suit various occasions. It can be seen that when the carbon source content added before the first sintering is increased from 1% to 3% (ie, Example 2 and Example 3), the compaction decreases by 5.19%, the resistivity increases by more than 5 times, and the D50 increases by 19.46%, which shows that the amount of carbon content added before the first sintering has a more obvious effect on the conventional indicators of the finished product.
[0168] Among them, the resistivity of the finished product of Example 3 reaches 325.8Ω·cm mainly because: the total amount of carbon added in step 1 and step 3 of the present application embodiment must be consistent, and the amount of carbon source added in step 3 has a greater impact on the resistivity, and the more added, the lower the resistivity. In Example 3, the carbon source added in step 1 is 3%, and the amount of carbon source added in step 3 is only 9%. The amount of carbon source added in step 3 is reduced, resulting in an increase in the resistivity of the finished product of Example 3.
[0169] At the same time, it was found that the resistivity of Comparative Example 1 was relatively large, and the compaction was the smallest among all samples, which indicates that directly adding all carbon sources before sintering is not conducive to the conventional indicators of the finished product. Comparative Example 2 is a sample using glucose as a single carbon source. It can be seen that the compaction is not high, and the specific surface area is large, which is not conducive to the processing performance of the material. Comparative Example 3 is a sample using polyvinyl alcohol as a single carbon source. It can be seen that the compaction is good, but the specific surface area is very low. This is because the polymer macromolecule is coated with a dense carbon layer on the surface of the particles during sintering, resulting in larger finished particles and lower porosity, which is not conducive to the transmission of lithium ions.
[0170] 7. The X-ray diffraction pattern of lithium manganese iron phosphate prepared in Example 1-3 is shown in the attached figure. Figure 2 As shown, it can be seen that the lithium manganese iron phosphate prepared in Examples 1-3 is in good agreement with the standard card (PDF#77-0178) of lithium manganese phosphate with an orthorhombic olivine structure, proving that the lithium manganese iron phosphate is successfully prepared with good crystallinity, and proving that the method strategy is feasible.
[0171] 8. The scanning electron microscope images of the lithium manganese iron phosphate prepared in Examples 1-3 and Comparative Examples 1-3 are shown in the attached figure. Figure 3 As shown, it can be seen that the lithium manganese iron phosphate prepared in the examples all have spherical or elliptical morphological features. After comparison, it can be found that: the sample in Example 1 rarely has particle agglomeration, the particle consistency is the best, and the sphericity is the highest. The material particles in Example 2 are larger, and the lithium ion transmission path is longer, which is not conducive to the electrochemical performance to a certain extent. The particle agglomeration in Example 3 is relatively serious, which is not conducive to the contact between the material and the electrolyte to a certain extent, and is also not conducive to the electrochemical performance.
[0172] However, the lithium manganese iron phosphate prepared in Comparative Example 1 is seriously agglomerated, which is because more carbon sources are added before the first sintering, forming more extremely small particles and causing serious agglomeration. In Comparative Example 2, only a short carbon chain carbon source such as glucose is added, and the carbon coating layer is not uniform, and the size of the particles is quite different, so the material is prone to side reactions with the electrolyte. In Comparative Example 3, only a high molecular polymer carbon source such as polyvinyl alcohol is added, and the carbon coating layer is too dense, which reduces the specific surface area of the material, thereby reducing the active sites of the material, and at the same time, the electronic conductivity of the material decreases significantly, which makes the material very polarized when the electrochemical reaction occurs in the battery, which is very unfavorable to the electrical performance.
[0173] 9. Attachment Figure 4 This is the transmission electron microscope image of Example 1, which clearly shows that it has a good carbon coating layer, which is the main reason for its high manganese platform retention rate.
[0174] 10. In order to explore the electrochemical properties of lithium manganese iron phosphate prepared in the examples and comparative examples, the LAND electrochemical testing system was used to test the electrochemical properties of the materials, which specifically included the following steps:
[0175] ① First, pass the prepared lithium manganese iron phosphate positive electrode material through a 200-mesh sieve, and then place it in a watch glass and dry it for more than 2 hours at a drying temperature of 130°C to fully remove moisture;
[0176] ② Mix the dried lithium manganese iron phosphate positive electrode material with conductive carbon black, polyvinylidene fluoride (PVDF), dispersant and N-methylpyrrolidone (NMP) in a 100mL ball mill jar. Use zirconium oxide beads as the ball mill beads. Mix the large and small beads in a ratio of 1:1. Stir the beads in the ball mill at a rate of 450r / min for 3h to obtain a positive electrode slurry for a lithium-ion battery with an active material content of 91%;
[0177] ③ The positive electrode slurry is evenly coated on the aluminum foil with a carbon layer by a coating machine, and then dried at 120°C for 10 minutes, followed by roller pressing at a pressure of 12MPa, and then a sheet making machine of a certain specification is used to make a suitable positive electrode sheet, and the active material content is weighed to calculate the subsequent charge and discharge specific capacity;
[0178] ④ Fix the prepared positive electrode plate on the positive electrode shell with glue to avoid the occurrence of the plate offset when the positive electrode shell is placed at the end. After fixing, dry it at 130℃ for more than two hours to completely remove the dispersant NMP. At the same time, the negative electrode shell, shrapnel, and steel sheet should be ultrasonically cleaned and dried for use;
[0179] ⑤ Start assembling button cells in the glove box, ensuring that the moisture and oxygen contents are below 0.5ppm. First, place the negative electrode shell at the bottom, place the spring on it, and then place the steel sheet and lithium sheet negative electrodes in order, then drop LiPF dissolved in a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) 6 80μL of electrolyte, then place Celgard 2500 separator, then add another 80μL of electrolyte, and place the positive electrode shell with the positive electrode sheet attached. Finally, put the preliminarily assembled battery into the tablet press for tableting, set the pressure to 650Kg, switch the speed to 4.0s, keep the pressure for 1.5s, place the battery in the middle with the negative electrode on top, wipe off the overflowed electrolyte after tableting, and the battery assembly is completed.
[0180] ⑥ The electrochemical performance of the button cell was tested using the LAND electrochemical test system. The discharge cut-off voltage was set to 2.0 V, the charge cut-off voltage was set to 4.3 V, and the nominal specific capacity was set to 150 mAh g -1 The charge and discharge curves of lithium manganese iron phosphate positive electrode active materials at 0.1C and 1C rates, the cycle curves at 1C conditions at different temperatures, and the rate curves at 0.1C, 0.5C, 1C, 2C, and 3C conditions at room temperature were tested respectively.
[0181] Among them, the test results of the charge and discharge performance under 0.1C and 1C conditions at room temperature are shown in Table 2 below:
[0182] Table 2
[0183]
[0184] From the charge and discharge performance of each lithium iron phosphate finished product at room temperature and 0.1C and 1C conditions in Table 2 above, it can be seen that Example 1 in which 2% carbon content is added before the first sintering has the best charge-withdrawal performance. When the carbon content before the first sintering is increased from 1% to 3%, the charge-withdrawal performance first increases and then decreases, but the performance of the 3% addition is better than the charge-withdrawal performance of 1%. At the same time, it can also be observed that adding too high a carbon source before the first sintering (Comparative Example 4), adding a lower carbon source before the first sintering (Comparative Example 5), adding all carbon sources before the first sintering (Comparative Example 1) or adding a single carbon source before the first sintering (Comparative Examples 2 and 3) are not conducive to the performance of the material's charge-withdrawal performance.
[0185] In addition, the charge and discharge curves of the lithium manganese iron phosphate prepared in Examples 1-3 and Comparative Examples 1-3 under 0.1C and 1C conditions are shown in the attached figure. Figure 5 As shown, it can be seen that the lithium manganese iron phosphate prepared in Example 1 has the best button half-cell performance under 0.1C and 1C conditions.
[0186] Attached Figure 6 The discharge specific capacity of the lithium manganese iron phosphate prepared in Examples 1-3 and Comparative Examples 1-3 when cycled under 1C conditions is shown. Figure 7 The discharge manganese platform retention rate of lithium manganese iron phosphate prepared by Examples 1-3 and Comparative Examples 1-3 when cycled under 1C conditions is shown. It can be found that after a certain number of cycles, the discharge specific capacity of each material tends to be stable, but their manganese platform retention rate shows a trend of continuous decay. Among them, the sample in Example 1 can still maintain a manganese platform discharge retention rate of 52.25% after 100 cycles, while the manganese platform retention rates of Examples 2-3 and Comparative Examples 1-3 after cycling are 14.49%, 43.74%, 22.21%, 26.46%, and 23.47%, respectively. It can be seen that the sample prepared in Example 1 has a very obvious advantage.
[0187] Attached Figure 8 The discharge specific capacity of the lithium manganese iron phosphate prepared in Examples 1-3 and Comparative Examples 1-3 under 1C condition at 40°C is shown; Fig. 9 The discharge manganese platform retention rate of lithium manganese iron phosphate prepared by Examples 1-3 and Comparative Examples 1-3 under 1C conditions at 40°C is shown. It can be found that after a certain number of cycles, the discharge specific capacity of each material tends to be stable, but their manganese platform retention rate shows a trend of continuous decay. Among them, the sample in Example 1 can still maintain a manganese platform discharge retention rate of 57.58% after 100 cycles, while the manganese platform retention rates of Examples 2-3 and Comparative Examples 1-3 after cycling are 20.01%, 50.42%, 35.45%, 42.46%, and 33.21%, respectively. It can be seen that the sample prepared in Example 1 has a very obvious advantage.
[0188] The discharge specific energy is obtained by multiplying the discharge specific capacity by the discharge voltage. It can also be seen that the lithium manganese iron phosphate prepared in Example 1 has excellent performance, and the discharge specific capacity has almost no attenuation after the cycle. At the same time, it is found that the sample prepared in Example 1 also has almost no capacity climbing phenomenon, which indicates that the polarization degree of the material is relatively small.
[0189] Attached Fig.10 The figure is a rate curve of Examples 1-3 at 25°C and 0.1C, 0.5C, 1C, 2C, and 3C conditions; it can be seen that the capacity attenuation and the attenuation area of the manganese-stage discharge platform ratio at high rate in Example 1 are significantly smaller than those in Example 2, while Example 3 performs better at high temperature than at room temperature, and the attenuation of the manganese-stage discharge platform ratio is close to that of Example 1.
[0190] Attached Fig.11 The figure is a graph showing the change of the manganese stage discharge platform retention rate of Examples 1-3 at 25°C under 0.1C, 0.5C, 1C, 2C, and 3C conditions. It can be seen that the proportion of the manganese stage discharge platform in Example 1 as the rate increases is 62.56%, 62.59, 61.21%, 57%, and 52.77% respectively; the proportion of the manganese stage discharge platform in Example 2 as the rate increases is 64%, 57.4%, 47.77%, 36.03%, and 27.13% respectively; the proportion of the manganese stage discharge platform in Example 3 as the rate increases is 63.1%, 63.14%, 60.47%, 54.42%, and 48.92% respectively. It can be seen that the finished product prepared in Example 1 has obvious advantages when double charging and discharging.
[0191] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a manganese phosphate-based positive electrode material, characterized in that: The following steps are involved: Obtaining raw material components including a phosphorus source, a manganese source, a lithium source, other metal sources and an initial carbon source, preparing a first mixed slurry with the raw material components and a first solvent, and then drying the mixed slurry to obtain a primary mixed material; the mass percentage of the initial carbon source in the raw material components is 1% to 3%; Under an inert atmosphere, the mixed material is subjected to a primary sintering treatment to obtain a primary sintered material; The amount of additional carbon source required is calculated according to the carbon content in the primary sintered material and the target carbon content in the finished product, and the primary sintered material, the additional carbon source and the second solvent are made into a second mixed slurry and then dried to obtain a secondary mixed material; wherein the initial carbon source and the additional carbon source independently include a polymer carbon source and a short-chain carbon source respectively; Under an inert atmosphere, the secondary mixed material is subjected to a secondary sintering treatment and then crushed to obtain the finished product, namely, the manganese phosphate-based positive electrode material.
2. The method for preparing a manganese phosphate-based positive electrode material according to claim 1, wherein: The mass percentage of the initial carbon source in the raw material component is 1.5% to 2.5%; And / or, the carbon content in the primary sintering material is 0.12% to 0.36%; and / or, the amount of the additional carbon source added is 8% to 12% of the total mass of the primary sintering material and the additional carbon source; And / or, the target carbon content in the finished product is 1.6% to 1.65%.
3. The method for preparing a manganese phosphate-based positive electrode material according to claim 2, characterized in that: The actual carbon content in the manganese phosphate-based positive electrode material is 1.4% to 1.6%; And / or, the D50 particle size of the manganese phosphate-based positive electrode material is 0.9 μm to 1.5 μm; And / or, the compaction density of the manganese phosphate-based positive electrode material is greater than 2.19 g / cm 3 ; And / or, the specific surface area of the manganese phosphate-based positive electrode material is 15 m 2 / g~18m 2 / g; And / or, the resistivity of the manganese phosphate-based positive electrode material is lower than 200Ω·cm.
4. The method for preparing a manganese phosphate-based positive electrode material according to any one of claims 1 to 3, characterized in that: The polymer carbon source includes at least one of polyethylene glycol, polyvinyl alcohol, polyacrylic acid, carboxymethyl cellulose and starch; And / or, the short-chain carbon source includes at least one of glucose, sucrose, and citric acid; And / or, the other metal source includes: at least one of an iron source, a niobium source, a titanium source, a cobalt source, a nickel source, and a vanadium source; and / or, the first solvent and the second solvent each independently comprise water; And / or, the molar ratio of the other metal source to the manganese source is (10-X):X, wherein X is 2-8; And / or, the ratio of the total molar amount of the manganese source and the other metal source to the molar amount of the lithium source and the phosphorus source is 1:(1-1.03):(1-1.03).
5. The method for preparing a manganese phosphate-based positive electrode material according to claim 4, characterized in that: The first mixed slurry is prepared by a grinding process, and the particle size D50 of the material in the slurry is 0.6 μm to 0.9 μm; And / or, the conditions for drying the first mixed slurry include: spray drying under the conditions of atomization frequency conversion of 250 Hz to 350 Hz and inlet air temperature of 150° C. to 250° C.; And / or, the heating rate of the primary sintering treatment is 1°C / min to 10°C / min, the holding temperature is 400°C to 600°C, and the duration is 5h to 8h.
6. The method for preparing a manganese phosphate-based positive electrode material according to any one of claims 1 to 3 or 5, characterized in that: The second mixed slurry is prepared by a grinding process, and the particle size D50 of the material in the slurry is 0.6 μm to 0.9 μm; And / or, the conditions for drying the second mixed slurry include: spray drying under the conditions of atomization frequency of 250 Hz to 350 Hz and inlet air temperature of 150° C. to 250° C.; And / or, the heating rate of the secondary sintering treatment is 1°C / min to 10°C / min, the holding temperature is 600°C to 800°C, and the duration is 6h to 10h.
7. A manganese phosphate-based positive electrode material prepared by the method according to any one of claims 1 to 6, characterized in that: The invention comprises a manganese phosphate salt-based active inner core and a carbon layer coated on the outer surface of the inner core; the carbon layer is made of a polymer carbon source and a short-chain carbon source.
8. The manganese phosphate-based positive electrode material according to claim 7, characterized in that: The manganese phosphate-based active core includes lithium manganese iron phosphate; And / or, the thickness of the carbon layer in the manganese phosphate-based positive electrode material is 1 nm to 5 nm.
9. A positive electrode sheet, characterized in that: It comprises a current collector and a positive electrode active layer formed on the surface of the current collector, wherein the positive electrode active layer contains the manganese phosphate salt positive electrode material as described in any one of claims 1 to 6, or the manganese phosphate salt positive electrode material prepared by the method as described in any one of claims 7 to 8.
10. A secondary battery, characterized in that: The secondary battery comprises the positive electrode sheet as claimed in claim 9.
Citation Information
Patent Citations
High-capacity lithium ferric manganese phosphate positive electrode material and processing technology
CN114497565A
Carbon-coated lithium manganese iron phosphate composite material and preparation method thereof
CN114620703A
Water-based positive pole piece composition containing water-soluble lithium-containing compound, and secondary battery
WO2023245484A1
Cited By
Preparation method of lithium manganese iron phosphate positive electrode material and lithium manganese iron phosphate positive electrode material
CN120288731A
